2015
DOI: 10.1038/srep18425
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of circulating tumor DNA for molecular assessment in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal malignancies. The genomic landscape of the PDAC genome features four frequently mutated genes (KRAS, CDKN2A, TP53, and SMAD4) and dozens of candidate driver genes altered at low frequency, including potential clinical targets. Circulating cell-free DNA (cfDNA) is a promising resource to detect and monitor molecular characteristics of tumors. In the present study, we determined the mutational status of KRAS in plasma cfDNA using multiplex pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 45 publications
10
150
1
3
Order By: Relevance
“…This result suggested that ctDNA diffused into the systemic circulation in some cases. Indeed, ctDNA+ patients may be related to micrometastasis which cannot be found by imaging, as described by other researchers [35].Therefore, ctDNA+ patients should be considered for other options before IRE, such as moderate chemotherapy.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…This result suggested that ctDNA diffused into the systemic circulation in some cases. Indeed, ctDNA+ patients may be related to micrometastasis which cannot be found by imaging, as described by other researchers [35].Therefore, ctDNA+ patients should be considered for other options before IRE, such as moderate chemotherapy.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…However, while the proportion of cfDNA that is tumor-derived (the ctDNA fraction) is largely unknown in metastatic bladder cancer, it is often greater than 1% in advanced solid malignancies studied to date (24,37,38). In data from The Cancer Genome Atlas (TCGA), 98% of primary muscle-invasive bladder cancer had a nonsynonymous somatic mutation in at least one of 50 bladder cancer genes in our panel (13).…”
Section: High Ctdna Burden In Metastatic Bladder Cancermentioning
confidence: 99%
“…Subsequently, several proof of concept studies showed various tumour specific aberrations in the circulation such as mutation in oncogene and tumour suppressor gene (Sorenson et al 1994;Silva et al 1999b), microsatellite instability (Chen et al 1996) and aberrant DNA methylation (Silva et al 1999a). In recent years, studies are directed towards evaluating the clinical utility of ctDNA in the management of cancer (Takai et al 2015).…”
Section: The Biology Of Ctdnamentioning
confidence: 99%